Adventitious shoot regeneration from leaf and stem explants of Salix matsudana Koidz (Bangladesh Journal of Botany, 2020)
Currently, the leaf and stem as explants for rapid propagation in vitro remained unknown in Salix matsudana. Multiple shoots were regenerated from leaf and stem (stem apex and stem with axil). The optimum medium for callus regeneration and shoots induction from leaf was on WPM medium containing 6.0 mg/l zeatin (Z) and 0.75 mg/l NAA. The optimum medium of shoot induction from stem apex was on MS medium supplemented with 8.0 mg/l Z and 1.0 mg/l NAA, and from stem with axil was on MS with 8.0 mg/l Z and 0.5 mg/l NAA. Rooting of regenerated shoots was obtained on the same medium supplemented with 1.0 mg/l activated charcoal.